New approaches to creating a culture of innovation - Trompenaars, Fons; Woolliams, Peter (Emerald Publishing Limited, 2025)
In an era marked by the dominance of a few corporate giants, and the ease of replicating ideas at minimal costs, the imperative for organisations of all sizes to continually innovate has become paramount. Faced with this reality, CEOs increasingly perceive innovation as the key to fostering organic growth and enhancing brand equity. Rather than confining innovation to product or process development, business leaders are pivoting towards innovative business model differentiation as a cornerstone of success. New Approaches to Creating a Culture of Innovation offers fascinating insights into how companies can embrace innovation and make it work for them at both a personal and company level. Drawing on extensive market research, business gurus Fons Trompenaars and Peter Woolliams outline effective innovation strategies that can be implemented at scale. This original work will appeal to specialists in all areas of management and leadership, HR professionals giving support to the development of individuals and teams, leaders involved in changing their corporate culture, employees wanting to exert their creativity, and business studies students at both undergraduate and MBA levels. Purchase of this book includes exclusive access to app-based content, enabling readers to explore the application of specific concepts in further detail.
Includes index.
Keywords: Creative ability in business.; Business & Economics -- Development -- General.; Business innovation.; Development economics and emerging economies.; elektronické knihy; electronic books